ANALISIS SEMIOTIK REPRESENTASI MASKULINITAS PADA IKLAN BCA “DON’T KNOW? KASIH NO!” - Ridwan Omaryanto, Osama (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
The aim of this research is to find out how the representation of masculinity is constructed in the BCA advertisement "Don't Know? Give No using Rolan Bartes' semiotic analysis. The research method used is a descriptive qualitative method by describing research results and using data analysis methods by means of documentation and observation of research objects to make meaning using the theory used. The results of this research. In the BCA advertisement, there are three different myths representing masculinity, namely men are brave beings, men are leaders, men are rulers. The representation of masculinity in men built in advertisements is visualized as men who think critically, act calmly (slow down) and are brave men. A message that the community wants to convey to consumers is that taking a stand in dealing with fraudulent methods can increase the awareness of BCA customers to be more careful and always think critically to protect personal data.